Analysis of the Impact of Foreign Direct Investment (FDI) on Industrial Productivity and Labour Welfare in ASEAN Countries: A Panel Econometric Approach - Alimuddin, Alimuddin; Suriyanti, Suriyanti (SEIKO : Journal of Management & Business, 2024)
This study aims to analyze the impact of foreign direct investment (FDI) on industrial productivity and labor welfare in ASEAN countries. FDI growth has become an important phenomenon in the global economic context, especially in the ASEAN region which is an investment destination that is increasingly in demand by foreign investors. Econometric approaches were used to examine the relationship between FDI, industrial productivity, and labor welfare using panel data from ASEAN countries over a period of time. The results of the analysis show that FDI has a significant impact on industrial productivity in ASEAN countries. The study also found that FDI contributes to improving workforce well-being through job creation, technology transfer, and income generation. However, these effects may vary between ASEAN countries, depending on factors such as labor market regulation, education levels, and infrastructure. The policy implication of this study is the importance of supporting foreign direct investment as one of the important factors in promoting economic growth and improving welfare in ASEAN countries. However, the government also needs to pay attention to policies that facilitate technology transfer and improve the quality of labor so that the benefits of FDI can be maximized by the community. In this regard, it is important for the government to provide appropriate incentives and create a conducive business environment for foreign investors, while still paying attention to environmental sustainability and protection of workers' rights. In addition, the research provides valuable insights for policymakers and stakeholders to improve the investment environment and effectively harness FDI's potential for sustainable economic development in ASEAN. Keywords: Foreign Direct Investment (FDI), Industrial Productivity, Labour Welfare, ASEAN Countries, Panel Econometric Approach